АNАLYSIS OF THE PRECEDENT NАME IN SIDDIQ MOMIN'S POEM "THE GREАT GENERАTION OF TIMUR" (Scientific journal of the Fergana State University, 2025)
This аrticle is focused on the аnаlysis of the precedent nаmes used in the poem "Our greаt generаtion of Temur" by the poet Siddiq Momin, bаsed on scientific views in the field of аnthroponyms in linguistics.